The role of potential probiotic strains Lactobacillus reuteri in various intestinal diseases: New roles for an old player - Yu, Zihan; Chen, Jihua; Liu, Yaxin; Meng, Qingguo; Liu, Hang; Yao, Qinyan; Song, Wenxuan; Ren, Xiangfeng; Chen, Xin (Frontiers in Microbiology, 2023)
Lactobacillus reuteri (L. reuteri), a type of Lactobacillus spp., is a gut symbiont that can colonize many mammals. Since it was first isolated in 1962, a multitude of research has been conducted to investigate its function and unique role in different diseases as an essential probiotic. Among these, the basic functions, beneficial effects, and underlying mechanisms of L. reuteri have been noticed and understood profoundly in intestinal diseases. The origins of L. reuteri strains are diverse, with humans, rats, and piglets being the most common. With numerous L. reuteri strains playing significant roles in different intestinal diseases, DSM 17938 is the most widely used in humans, especially in children. The mechanisms by which L. reuteri improves intestinal disorders include protecting the gut barrier, suppressing inflammation and the immune response, regulating the gut microbiota and its metabolism, and inhibiting oxidative stress. While a growing body of studies focused on L. reuteri, there are still many unknowns concerning its curative effects, clinical safety, and precise mechanisms. In this review, we initially interpreted the basic functions of L. reuteri and its related metabolites. Then, we comprehensively summarized its functions in different intestinal diseases, including inflammatory bowel disease, colorectal cancer, infection-associated bowel diseases, and pediatric intestinal disorders. We also highlighted some important molecules in relation to the underlying mechanisms. In conclusion, L. reuteri has the potential to exert a beneficial impact on intestinal diseases, which should be further explored to obtain better clinical application and therapeutic effects.